Coordination Failures in Network Migration - Axel Heitmüller (Institute for the Study of Labor (IZA), 2003)
Previous migration facilitates future population moves, a phenomenon called network migration. However, thus far, network migration has been closely linked to network externalities. In contrast, this paper argues that the incumbent migration population can actively impact on future migration flows, yet fails to achieve a Pareto optimal network size due to coordination failures. In short, it stresses the active role incumbents take in the provision of network effects and, second, it provides theoretical evidence that selfperpetuating and sustained immigration is not at odds with rational acting individuals and must not simply be ascribed to pure network externalities.
Keywords: J61; C70; J60; 330; household migration networks; Pareto optimality; optimal network size; network externalities; Einwanderung; Migrationstheorie; Soziales Netzwerk; Theorie